Livestock Insurance Adoption in Rural Nepal: A Behavioral Analysis - Thapa, Bharat Singh; Bhandari, Rachana; Pathak, Durga Datt (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study explores the behavioral and contextual factors influencing the adoption of livestock insurance in rural Nepal, drawing on the integrative frameworks of the Theory of Planned Behavior (TPB) and the Theory of Reasoned Action (TRA). Design/methodology/approach: A cross-sectional survey was conducted among 300 farmers in Tinpatan Rural Municipality, Sindhuli. Logistic regression was used to assess adoption likelihood, and Smart PLS-SEM validated the model and structural relationships. Findings: The study found that social, economic, regulatory, and occupational factors significantly influence the adoption of livestock insurance among rural farmers in Nepal. Economic factors had the strongest effect, followed by social factors, regulatory factors, and occupational factors. These results suggest that higher income, awareness, access to subsidies, community influence, transparent policies, and institutional trust all contribute positively to adoption. Conclusion: Increasing awareness, simplifying procedures, enhancing policy transparency, and strengthening institutional support are crucial strategies for promoting livestock insurance uptake among rural farmers. Implications: The findings provide insights for policymakers, insurers, and development agencies to design farmer-centric insurance schemes. Tailored awareness campaigns, streamlined claim processes, and stronger local support mechanisms can make livestock insurance more inclusive. Originality/value: This study integrates behavioral theories with socio-economic determinants, addressing a critical gap overlooked in studies focused mainly on developed economies. JFL Classification: G22, Q12, Q14, D81, O13